Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0087549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abdominal Obesity in Spanish Children and Adolescents. Do We Need Waist Circumference Measurements in Pediatric Practice?

Abstract: BackgroundEvidence indicates that central adiposity has increased to a higher degree than general adiposity in children and adolescents in recent decades. However, waist circumference is not a routine measurement in clinical practice.ObjectiveThis study aimed to determine the prevalence of abdominal obesity based on waist circumferences (WC) and waist to height ratio (WHtR) in Spanish children and adolescents aged 6 to 17 years. Further, the prevalence of abdominal obesity (AO) among normal and overweight indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
7
17

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 28 publications
7
77
7
17
Order By: Relevance
“…The 10.6% prevalence of AO found in this study is below the values found for adolescents in Spain (11.6%)5 and USA (34.7%),1 and similar to those found for South Korean adolescents (8.4%) 1. When compared to studies performed in Brazil, the found prevalence of AO was higher than the values reported for Minas Gerais (Januária) (2.1%)7 and lower than the values reported for Maranhão (22.7%)6 and Curitiba (12.2%) 8.…”
Section: Discussioncontrasting
confidence: 92%
“…The 10.6% prevalence of AO found in this study is below the values found for adolescents in Spain (11.6%)5 and USA (34.7%),1 and similar to those found for South Korean adolescents (8.4%) 1. When compared to studies performed in Brazil, the found prevalence of AO was higher than the values reported for Minas Gerais (Januária) (2.1%)7 and lower than the values reported for Maranhão (22.7%)6 and Curitiba (12.2%) 8.…”
Section: Discussioncontrasting
confidence: 92%
“…At present, 38.6% of Spanish children and adolescents are overweight or obese [1], and 16.5% have abdominal obesity [2]. The high obesity prevalence is of concern because premature onset of related illnesses such as diabetes, hypercholesterolaemia and non-alcoholic fatty liver disease is increased among obese children [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…La obesidad abdominal en el grupo de madres se aproxima a lo encontrado en los Estados Unidos, donde en adultos se ha mantenido alrededor del 50% desde 1999, y en el periodo 2009-2010 dicha prevalencia fue de 46,4% en varones y 65,4% en mujeres (33) . Por otro lado, la magnitud de obesidad abdominal en adolescentes de nuestro estudio (5,6%), es inferior a lo encontrado en adolescentes españoles de 12 a 17 años en quienes se reporta un 11,6% (36) , y en adolescentes norteamericanos de 12 a 18 años en quienes la prevalencia (periodo 2011-2012) fue 22,4% (37) .…”
Section: Discussionunclassified